2016
DOI: 10.1167/iovs.16-20551
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Mitochondrial Integrity, Telomere Length, and Sensitivity to Oxidation by In Vitro Culture of Fuchs' Endothelial Corneal Dystrophy Cells

Abstract: Citation: Gendron SP, Thériault M, Proulx S, Brunette I, Rochette PJ. Restoration of mitochondrial integrity, telomere length, and sensitivity to oxidation by in vitro culture of Fuchs' endothelial corneal dystrophy cells. Invest Ophthalmol Vis Sci. 2016;57:5926-5934. DOI:10.1167/ iovs.16-20551 PURPOSE. Fuchs' endothelial corneal dystrophy (FECD), a degenerative disease of the corneal endothelium that leads to vision loss, is a leading cause of corneal transplantation. The cause of this disease is still u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 49 publications
2
14
0
Order By: Relevance
“…The goal of these experiments was to ascertain whether CECs from normal human corneas can be stimulated to proliferate in organ culture where the low basal proliferation may better reflect the in vivo situation 34 compared with dissociated culture systems that produce high levels of proliferation of normal and dystrophic/FECD CECs. 7,8,[44][45][46] In this human corneal organ culture model, unstimulated CECs in the mid zone had very few cells incorporating EdU, indicating that this model is more reflective of the in vivo situation where the number of cells changes only slowly.…”
Section: Discussionmentioning
confidence: 84%
“…The goal of these experiments was to ascertain whether CECs from normal human corneas can be stimulated to proliferate in organ culture where the low basal proliferation may better reflect the in vivo situation 34 compared with dissociated culture systems that produce high levels of proliferation of normal and dystrophic/FECD CECs. 7,8,[44][45][46] In this human corneal organ culture model, unstimulated CECs in the mid zone had very few cells incorporating EdU, indicating that this model is more reflective of the in vivo situation where the number of cells changes only slowly.…”
Section: Discussionmentioning
confidence: 84%
“…Total RNA was isolated from postconfluent CEC cultures, as described. 39 Passage 2 or 3 cells were grown and cultured for 24–38 days, with the addition of hydrocortisone (0.4 μg/mL) during the last 7 days of culture. Total RNA was isolated using the RNeasy Mini Kit (QIAGEN, Toronto, ON, CA) and RNA quality was analyzed using the 2100 Bioanalyzer (Agilent Technologies, Mississauga, ON, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…Descemet's membrane were kept overnight at 37 °C in growth medium, as previously described 10 . Explants were then washed with Opti-Mem-I (for all markers but CM-H 2 DCFDA; Invitrogen, Burlington, ON, Canada) or PBS (for CM-H 2 DCFDA).…”
Section: Markers Used On Fecd and Healthy Endothelium Explants Cornementioning
confidence: 99%
“…In this hypothetic vicious circle, mitochondria allow for a compensation mechanism for cell depletion, but this eventually leads to an energetic exhaustion that we call "mitochondrial burnout". We previously showed that, in the same FECD explant, individual CECs present different levels of mitochondrial mass 10 , suggesting that each CEC is not at the same stage of the vicious circle. In an attempt to decipher the chronology of events that leads to cell death in FECD, we analyzed the different elements of the vicious circle using human FECD corneal endothelial explants.…”
mentioning
confidence: 99%